Impact of Westernization on Ghanaian Culture and Fashion - Adade , Abena (International Journal of Fashion and Design, 2023)
Purpose: The study sought to analyze the impact of westernization on Ghanaian culture and fashion. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The results show that findings revealed that fashion is an accessible and flexible means of expressing modernity and there were some forms of fashion in terms of clothing, present among Ghanaians before Europeans arrived on the coast. Ghanaian fashion and the youth are being influenced by foreign factors with a mixture of both traditional and foreign design concepts to meet international standards. Unique Contribution to Theory, Practices and Policies: The trickle-down and trickle-up theory may be used to anchor future studies in the fashion sector. The study results will also benefit other stakeholders such as the policy makers as well as researchers and scholars from different parts of the world. The top management of fashion industry in the country will also use the study findings to improve the culture and ensure high and stable performance in all their activities and programs. The study recommends that the adoption of effective social protection development policies in the fashion industry will help to improve efficiency in their major operations and activities.